Appetite Sensations, Appetite Signaling Proteins, and Glucose in Obese Adolescents with Subclinical Binge Eating Disorder. (11th March 2014) - Adamo, Kristi B.; Wilson, Shanna L.; Ferraro, Zachary M.; Hadjiyannakis, Stasia; Doucet, Éric; Goldfield, Gary S.
Abstract : Objective . This study aimed to investigate potential differences in appetite sensations, ghrelin, peptide YY, and glucose and their relationship with energy and macronutrient intake in obese adolescents with subclinical binge eating disorder. Methods . Fifteen obese adolescents (six and nine individuals with and without subclinical binge eating disorder, resp.) qualified for this study. Visual analog scales and Three-Factor Eating Questionnaires were used to assess eating behaviours. Circulating ghrelin, peptide YY, and glucose were measured after fasting and at multiple time points postprandially following a standardized breakfast meal. Energy and macronutrient intake were measured with an ad libitum lunch buffet. Results . Emotional eating scores were significantly higher in obese adolescents with subclinical binge eating disorder. Hunger levels rose and satiety levels fell significantly over the course of the monitoring period but there was no difference between the two groups. Obese adolescents with subclinical binge eating disorder did not have significantly different levels of appetite signaling proteins or glucose. Obese adolescents with subclinical binge eating disorder had a nonsignificantly higher energy and macronutrient intake. Conclusions . A significant difference between the two groups in terms of their emotional eating scores highlights the important role that psychological factors play in relation to eating behaviours.